Sequential domain assembly of ribosomal protein S3 drives 40S subunit maturation - Valentin Mitterer (Nature Portfolio, 2016)
Ribosome biogenesis involves the hierarchical assembly of several proteins and RNA components. Here the authors describe a mechanism for ribosomal protein S3 incorporation into 40S ribosomal subunits that involves S3 dimerization and stepwise incorporation of two distinct S3 interaction domains coupled to release of ribosomal maturation factors.